Design and development of a new electromagnetic prime mover solenoid powered engine preliminary design - Bahrin S.Z.A.S.K.; Amirulddin U.A.U. (IEEE Computer Society, 2023)
The applications of electromagnetic prime mover devices are becoming more extensive as future technological developments are moving towards sustainable environment. From various types of electromagnetic prime mover devices, the most commonly used device is electric motor. However, this device has some major issues such as complex maintenance processes after catastrophic failure, complex/expensive controllers, and declining performance from the dependency of limited raw materials i.e. permanent magnets. These problems are mostly associated with the convenience in operation and certain problems are only applicable to certain types of electric motor. Due to these issues, the authors have developed a new electromagnetic prime mover design to replace the existing electric motor. This new prime mover is designed based on the solenoid concept and the internal combustion engine working mechanisms. In this paper, the authors are introducing a new electromagnetic prime mover design known as Solenoid Powered Engine (SPE). The paper describes the SPE conceptual design, mechanical components and combined electrical/electronic components. 2012 IEEE.